A 500kv and below voltage grade cable shielding material and its preparation method and application

CN122898060APending Publication Date: 2026-10-13ELECTRIC POWER RES INST CHINA SOUTHERN POWER GRID CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611100440.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-23
Publication Date
2026-10-13

AI Technical Summary

Technical Problem

这种分治策略存在固有不足,分散剂不具备捕获自由基的能力,无法抑制炭黑摩擦生热引发的焦烧;而常规抗氧剂直接加入基体树脂中,难以在炭黑/聚合物摩擦发热界面,即焦烧发生的高风险区域,形成有效富集

Benefits of technology

[0028]1.本发明3-(3,5-二叔丁基-4-羟基苯基)丙酸十八烷基酯中的受阻酚芳环能够与炭黑表面的石墨微晶结构产生π-π吸附,并可与炭黑表面的含氧基团产生氢键或偶极作用,使抗氧剂在炭黑表面形成稳定的抗氧化预吸附层。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122898060A_ABST
    Figure CN122898060A_ABST
Patent Text Reader

Abstract

The application provides a 500kV and below voltage grade cable shielding material and a preparation method and application thereof, the shielding material comprises, by weight, 58-76 parts of a base resin, 24-38 parts of conductive carbon black, 0.12-0.30 parts of 3-(3,5-di-tert-butyl-4-hydroxyphenyl) octadecyl propionate, 0.05-1.0 parts of a lubricant, 0.10-0.35 parts of an auxiliary antioxidant and 0.5-2.0 parts of a peroxide crosslinking agent; wherein 5%-20% of the total amount of 3-(3,5-di-tert-butyl-4-hydroxyphenyl) octadecyl propionate is located on the surface of the conductive carbon black to form an antioxidant pre-adsorption layer, and the rest is dispersed in the base resin phase, the hindered phenol aromatic ring of the antioxidant is adsorbed and combined with the surface of the carbon black, the octadecyl improves the compatibility of the carbon black and the resin, the phenolic hydroxyl group is enriched in the carbon black / polymer friction interface to capture free radicals nearby, and the pre-crosslinking is delayed and the processing scorching is inhibited. The application improves the carbon black dispersibility, the anti-scorching performance and the comprehensive mechanical properties under the premise of not increasing the total amount of the antioxidant, and is suitable for the shielding layer of 110kV and above crosslinked polyethylene insulated cables.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of polymer semiconducting shielding materials for cables, and more specifically, to a shielding material for cables with voltage levels of 500kV and below, its preparation method, and its application. Background Technology

[0002] The semi-conductive shielding layer of ultra-high voltage cables (110kV and above) is used to homogenize the electric field at the interface between the conductor and the insulation layer, and is a key functional layer to ensure the long-term safe operation of the cable. Semi-conductive shielding materials are usually based on ethylene copolymers as the matrix resin and conductive carbon black as the conductive filler, and cross-linking and shaping are achieved through peroxide cross-linking.

[0003] Two interrelated technical challenges exist in the extrusion processing of semiconductive shielding materials. First, the high surface energy and tendency of conductive carbon black particles to agglomerate lead to uneven conductive networks and decreased mechanical properties. Second, the frictional shear heat generated between carbon black and polymers can induce premature decomposition of the peroxide crosslinking agent, causing pre-crosslinking (scorching), resulting in rough extruded surfaces and deteriorated interface quality.

[0004] Conventional techniques typically treat carbon black dispersion and scorch prevention separately: dispersion relies on wax-based dispersants or coupling agents, while scorch prevention relies on scorch inhibitors or conventional antioxidants. This separate approach has inherent limitations: dispersants lack the ability to capture free radicals and cannot suppress scorch caused by frictional heating of carbon black; while conventional antioxidants, when directly added to the matrix resin, are difficult to effectively accumulate at the carbon black / polymer frictional heating interface, i.e., the high-risk region for scorch.

[0005] Furthermore, in carbon black-containing systems, hindered phenolic antioxidants are commonly adsorbed by carbon black. For a long time, the adsorption of antioxidants by carbon black has been considered a detrimental phenomenon in the field, and existing technologies have largely focused on avoiding or reducing this adsorption to prevent a decrease in the concentration of effective antioxidants in the matrix phase.

[0006] In summary, there is an urgent need in this field for a technical solution that can simultaneously address the dual problems of carbon black interfacial scorching and matrix thermo-oxidative stability without excessively increasing the amount of antioxidants or introducing additional dispersants. Summary of the Invention

[0007] In view of this, the present invention provides a cable shielding material for voltage levels of 500kV and below, its preparation method and application. The material uses octadecyl 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate as a carbon black interface functional additive. By pre-distributing a portion of the antioxidant to the surface of conductive carbon black to form an antioxidant pre-adsorption layer, and then dispersing the remaining portion in the matrix resin phase, the synergistic improvement of carbon black interface anti-scorching, carbon black dispersion improvement and matrix thermo-oxidative stability is achieved.

[0008] The technical solution of this invention is as follows:

[0009] In a first aspect, the present invention provides a cable shielding material for voltage levels of 500kV and below, wherein the shielding material is prepared by weight from raw materials comprising the following components:

[0010] The composition includes 58-76 parts of matrix resin, 24-38 parts of conductive carbon black, 0.12-0.30 parts of octadecyl 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, 0.05-1.0 parts of lubricant, 0.10-0.35 parts of antioxidant, and 0.5-2.0 parts of peroxide crosslinking agent.

[0011] Of the total amount of octadecyl 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, 5%-20% is pre-adsorbed onto the surface of the conductive carbon black, and the remainder is dispersed in the matrix resin phase.

[0012] Furthermore, the matrix resin includes one or more of ethylene-butyl acrylate copolymer, ethylene-vinyl acetate copolymer, ethylene-methacrylate copolymer, low-density polyethylene, and linear low-density polyethylene.

[0013] Furthermore, the conductive carbon black includes one or more of acetylene black, conductive furnace black, and Ketjen black, and the conductive carbon black has a specific surface area of ​​50-160 m² / g, a DBP oil absorption value of 100-380 mL / 100g, and an ash content of <0.5%.

[0014] Furthermore, the lubricant includes one or more of zinc stearate, calcium stearate, polyethylene wax, oxidized polyethylene wax, ethylene bis-stearamide, and organosilicon lubricants.

[0015] Furthermore, the antioxidant includes one or more of dioctadecyl thiodipropionate, dilauryl thiodipropionate, and phosphite antioxidants.

[0016] Furthermore, the peroxide crosslinking agent includes one or more of dicumyl peroxide, bis-tert-butylperoxypropylbenzene, and 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane.

[0017] Secondly, based on the same inventive concept, this invention provides a method for preparing cable shielding materials for voltage levels of 500kV and below as described in any of the first aspects, comprising the following steps:

[0018] The conductive carbon black is dried to remove water. The dried conductive carbon black is then pre-mixed with 5%-20% of the total amount of octadecyl 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate to pre-adsorb the ester onto the surface of the conductive carbon black, thus obtaining antioxidant pre-adsorbed carbon black.

[0019] The antioxidant pre-adsorbed carbon black, matrix resin, lubricant, antioxidant agent and the remaining octadecyl 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate were melt-blended and pelletized to obtain the compound.

[0020] After preheating the compound, a peroxide crosslinking agent is added for liquid-phase impregnation and adsorption to obtain the cable shielding material for voltage levels of 500kV and below.

[0021] Furthermore, the premixing temperature is 65-120℃, and the time is 5-30 min;

[0022] The melting and mixing temperature is 120-180℃, and the time is 5-20 minutes;

[0023] The preheating temperature is 50-75℃, and the time is 2-8 hours;

[0024] The liquid phase impregnation adsorption temperature is 45-70℃, and the time is 6-16h.

[0025] Furthermore, the premixing includes one of solvent-free hot premixing, solvent-assisted premixing, or melt spray premixing.

[0026] Thirdly, based on the same inventive concept, this invention provides the application of the 500kV and below voltage level cable shielding material described in the first aspect or the 500kV and below voltage level cable shielding material prepared by the preparation method described in the second aspect in the conductor shielding layer, insulation shielding layer or peelable semiconductive shielding layer of cross-linked polyethylene insulated cable of 110kV and above.

[0027] Compared with the prior art, the embodiments of the present invention have at least the following advantages or beneficial effects:

[0028] 1. The hindered phenolic aromatic ring in octadecyl 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate of the present invention can generate π-π adsorption with the graphite microcrystalline structure on the carbon black surface, and can generate hydrogen bonds or dipole interactions with the oxygen-containing groups on the carbon black surface, so that the antioxidant forms a stable antioxidant pre-adsorption layer on the carbon black surface.

[0029] 2. The octadecyl group in the octadecyl ester of 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate of the present invention can be inserted into or entangled in the ethylene polymer matrix, thereby improving the compatibility between carbon black and the matrix resin and reducing the secondary agglomeration and processing viscosity of carbon black.

[0030] 3. In this invention, after octadecyl 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate is pre-adsorbed onto the carbon black surface, its phenolic hydroxyl groups are enriched near the carbon black / polymer interface. This interface is prone to localized heating due to friction during high-shear mixing and extrusion, making it a high-risk area for premature decomposition of the peroxide crosslinking agent and processing scorching. The hindered phenolic structure pre-adsorbed on the carbon black surface can promptly capture initial free radicals in this high-risk area, reducing the free radical concentration at the interface, delaying the pre-crosslinking reaction, and thus effectively inhibiting processing scorching of the shielding material.

[0031] 4. This invention does not require a significant increase in the total amount of antioxidants, nor does it rely on a large amount of traditional scorch inhibitors. Therefore, it can maintain the efficiency of subsequent crosslinking and the overall performance of the shielding material while improving the anti-scorch performance.

[0032] 5. The technical concept of this invention is not to improve the performance of shielding materials by introducing additional ionomers, coupling agents or a large amount of scorch inhibitors, but to change the spatial distribution of octadecyl 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate without increasing the total amount of antioxidant, so that the same antioxidant plays different roles in the carbon black interface and the matrix resin phase. Attached Figure Description

[0033] To more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings used in the embodiments will be briefly introduced below. It should be understood that the following drawings only show some embodiments of the present invention and should not be regarded as a limitation of the scope. For those skilled in the art, other related drawings can be obtained based on these drawings without creative effort.

[0034] Figure 1 This is a schematic flowchart of the method for preparing cable shielding materials of voltage levels of 500kV and below according to the present invention. Detailed Implementation

[0035] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some, not all, of the embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0036] Unless otherwise specified, all raw materials, reagents, instruments and equipment used in this invention can be purchased from the market or prepared by existing methods.

[0037] It should be noted that the octadecyl 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate used in this invention, also known as antioxidant 1076, has the CAS number 2082-79-3. It has a hindered phenolic group and an octadecyl chain. The 3,5-di-tert-butyl-4-hydroxyphenyl structure of this antioxidant provides the function of hindered phenolic free radical scavenging, and the octadecyl chain provides compatibility with ethylene polymer matrices.

[0038] It should also be noted that antioxidant 1076 is a commonly used commercially available hindered phenolic antioxidant in the field, which can be used directly in this invention without requiring further synthesis by those skilled in the art.

[0039] To address the problems existing in the prior art, according to one aspect of the embodiments of this disclosure, a cable shielding material for voltage levels of 500kV and below is provided, which is prepared by weight from raw materials comprising the following components:

[0040] The composition includes 58-76 parts of matrix resin, 24-38 parts of conductive carbon black, 0.12-0.30 parts of octadecyl 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, 0.05-1.0 parts of lubricant, 0.10-0.35 parts of antioxidant, and 0.5-2.0 parts of peroxide crosslinking agent.

[0041] Of the total amount of octadecyl 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, 5%-20% is pre-adsorbed on the surface of conductive carbon black, and the remainder is dispersed in the matrix resin phase.

[0042] It should be noted that this invention reverses the well-known problem of carbon black adsorption and deactivation of antioxidants, which is recognized in the prior art, and utilizes it as an interface protection strategy. Specifically, antioxidant 1076 is divided into two parts: a small portion (5%-20% of the total) is pre-adsorbed onto the surface of conductive carbon black to form an antioxidant pre-adsorption layer; the majority remains in the matrix resin phase to maintain the overall thermo-oxidative stability of the matrix. The hindered phenolic aromatic rings pre-adsorbed on the carbon black surface bind to the carbon black graphite microcrystalline layer through π-π interactions. The phenolic hydroxyl groups are enriched near the carbon black / polymer triboelectric interface, capturing free radicals induced by shear friction nearby, inhibiting premature decomposition of peroxide crosslinking agents and processing scorching; the octadecyl groups at the ends of the hindered phenol molecules also improve the compatibility between carbon black and the matrix resin. The two parts of the antioxidant each perform their respective functions and work synergistically to achieve a triple synergistic optimization of carbon black interface anti-scorching, improved carbon black dispersion, and matrix thermo-oxidative stability without increasing the total amount of antioxidant.

[0043] In this invention, antioxidant 1076 is the core component for achieving the biphasic partitioning strategy. This antioxidant molecule consists of three parts: a hindered phenolic aromatic ring, a phenolic hydroxyl group, and an octadecyl group. The hindered phenolic aromatic ring provides free radical scavenging functionality, the phenolic hydroxyl group forms hydrogen bonds and dipole interactions with oxygen-containing functional groups on the carbon black surface, and the octadecyl group provides compatibility with the matrix resin. The synergistic effect of these three parts allows the antioxidant to both firmly pre-adsorb onto the carbon black surface to provide interfacial protection and to be well-dispersed in the matrix resin phase to provide matrix stabilization.

[0044] In some examples, the amount of antioxidant 1076 pre-mixed with conductive carbon black is 0.03%-0.13% of the mass of conductive carbon black. When the pre-addition amount is less than 0.03%, the coverage of the antioxidant pre-adsorption layer on the carbon black surface is insufficient, and the interface protection effect is not obvious; when it is greater than 0.13%, too much antioxidant occupies the active sites on the carbon black surface, which may interfere with the construction of the conductive network of carbon black.

[0045] In some examples, the total amount of antioxidant 1076 is preferably 0.12-0.30 parts, of which the amount pre-mixed with conductive carbon black is preferably 0.01-0.04 parts, and the amount dispersed in the matrix resin phase is preferably 0.08-0.25 parts. When the total amount of antioxidant is less than 0.12 parts, an effective pre-adsorption layer cannot be formed on the carbon black surface, and the thermo-oxidative stability of the matrix is ​​insufficient; when it is more than 0.30 parts, excessive antioxidant will excessively consume crosslinking agent free radicals, resulting in a decrease in crosslinking density. When the proportion of antioxidant on the carbon black surface is less than 5%, the interface protection effect is not obvious; when it is more than 20%, the antioxidant concentration in the matrix phase is insufficient, and the thermo-oxidative stability of the matrix decreases.

[0046] Preferably, 10%-20% of the total amount of antioxidant 1076 is located on the surface of the conductive carbon black.

[0047] In some examples, the matrix resin includes one or more of ethylene-butyl acrylate copolymer, ethylene-vinyl acetate copolymer, ethylene-methacrylate copolymer, low-density polyethylene, and linear low-density polyethylene.

[0048] Preferably, the matrix resin is a composite of ethylene-butyl acrylate copolymer and low-density polyethylene. The synergistic use of the two helps to balance the flexibility, melt processability and compatibility with carbon black of the shielding material.

[0049] In some examples, the lubricant includes one or more of zinc stearate, calcium stearate, polyethylene wax, oxidized polyethylene wax, ethylene bis-stearamide, and silicone lubricants. The addition of a lubricant helps improve melt flowability, but its dosage must be controlled within a reasonable range to avoid affecting the conductive network construction of the carbon black.

[0050] In some examples, the conductive carbon black includes one or more of acetylene black, conductive furnace black, and Ketjen black. In some examples, the conductive carbon black has a BET specific surface area of ​​50-160 m² / g, a DBP oil absorption value of 100-380 mL / 100g, and an ash content of <0.5%. Selecting conductive carbon black within the above parameter range is beneficial for providing sufficient specific surface area for antioxidant pre-adsorption, while ensuring the high purity of the carbon black to meet the stringent electrical performance requirements of cable shielding materials for voltage levels of 500kV and below.

[0051] In some examples, the co-antioxidant includes one or more of dioctadecyl thiodipropionate, dilauryl thiodipropionate, and phosphite antioxidants. The co-antioxidant works synergistically with hindered phenolic primary antioxidants to decompose hydroperoxides, further enhancing the material's thermo-oxidative stability.

[0052] In some examples, the peroxide crosslinking agent includes one or more of dicumyl peroxide, bis-tert-butylperoxypropylbenzene, and 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane.

[0053] Please refer to Figure 1 According to another aspect of the embodiments of this application, a method for preparing cable shielding materials with voltage levels of 500kV and below is also provided, comprising the following steps:

[0054] The conductive carbon black is dried to remove water. The dried conductive carbon black is then pre-mixed with 5%-20% of the total amount of octadecyl 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate to pre-adsorb the ester onto the surface of the conductive carbon black, thus obtaining antioxidant pre-adsorbed carbon black.

[0055] The antioxidant pre-adsorbed carbon black, matrix resin, lubricant, antioxidant agent and the remaining octadecyl 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate were melt-blended and pelletized to obtain the compound.

[0056] After preheating the compound, a peroxide crosslinking agent is added for liquid-phase impregnation and adsorption to obtain cable shielding material for voltage levels of 500kV and below.

[0057] It should be noted that in the above preparation method, the step of pre-mixing a portion of the antioxidant with carbon black separately to form antioxidant pre-adsorbed carbon black achieves two key functions: First, it allows the hindered phenolic antioxidant to be firmly pre-adsorbed onto the carbon black surface through π-π interactions, making it less prone to desorption during subsequent melt mixing and ensuring the stable existence of the antioxidant protective layer at the interface between carbon black and polymer; second, the pre-adsorbed antioxidant occupies some high-energy sites on the carbon black surface, reducing the surface energy of the carbon black particles and facilitating the uniform dispersion of carbon black in the matrix resin during mixing. The subsequent crosslinking agent adsorption step, performed at a lower temperature, ensures that the crosslinking agent is uniformly coated on the particle surface, preventing premature decomposition during the high-temperature mixing stage.

[0058] In some examples, the premixing of conductive carbon black and antioxidant 1076 can be achieved using any of the following methods: solvent-free thermal premixing, solvent-assisted premixing, or melt-spray premixing. When using solvent-free thermal premixing, conductive carbon black and antioxidant 1076 are mixed at high speed at 65-120°C for 5-30 minutes, allowing the antioxidant to melt and uniformly spread and adsorb onto the carbon black surface. When using solvent-assisted premixing, conductive carbon black and antioxidant 1076 are dispersed in organic solvents such as toluene, xylene, n-heptane, cyclohexane, or ethyl acetate. After ultrasonic or high-speed shearing treatment, the solvent is removed, allowing the antioxidant to be uniformly loaded onto the carbon black surface. When using melt-spray premixing, molten antioxidant 1076 is uniformly applied to the stirred conductive carbon black by spraying. All three premixing methods can be completed before the addition of the matrix resin, ensuring that the pre-adsorption of the antioxidant on the carbon black surface is not interfered with by competition from the matrix resin.

[0059] In some examples, the amount of antioxidant 1076 pre-mixed with conductive carbon black is 0.03%-0.13% of the mass of conductive carbon black. When the pre-addition amount is less than 0.03%, the coverage of the antioxidant pre-adsorption layer on the carbon black surface is insufficient, and the interface protection effect is not obvious; when it is greater than 0.13%, too much antioxidant occupies the active sites on the carbon black surface, which may interfere with the construction of the conductive network of carbon black.

[0060] In some examples, the premixing temperature is 65-120℃ for 5-30 minutes. This temperature range ensures that the antioxidant fully melts and spreads evenly on the carbon black surface, while remaining well below the decomposition temperature of the peroxide crosslinking agent. The melt mixing temperature is 120-180℃ for 5-20 minutes. The preheating temperature is 50-75℃ for 2-8 hours; the liquid phase impregnation adsorption temperature is 45-70℃ for 6-16 hours.

[0061] In some examples, the premixing of conductive carbon black and antioxidant 1076 is completed before the addition of the matrix resin, and no additional conventional scorch inhibitors are added during the subsequent melt mixing process, or the amount of conventional scorch inhibitors added is less than 0.1 parts. Since the antioxidant 1076 of this invention forms an antioxidant pre-adsorption layer on the carbon black surface that can effectively resist scorch at the carbon black / polymer frictional heating interface, pre-crosslinking during processing can be suppressed without relying on additional scorch inhibitors, thereby avoiding the adverse effects of conventional scorch inhibitors on subsequent crosslinking efficiency and overall material performance.

[0062] According to another aspect of the embodiments of this application, the application of a 500kV and below voltage level cable shielding material as described in any of the first aspects or a 500kV and below voltage level cable shielding material prepared by any of the preparation methods described in any of the second aspects is provided in the conductor shielding layer, insulation shielding layer or peelable semiconductive shielding layer of a 110kV and above cross-linked polyethylene insulated cable is also provided.

[0063] The present invention will be further illustrated below with reference to specific embodiments. All raw materials used in the following embodiments are commercially available products; the sample preparation conditions, test temperature, load, time, applicable standards, and calculation methods for each performance test are specifically described in the corresponding test.

[0064] Example 1

[0065] This embodiment 1 provides a cable shielding material for voltage levels of 500kV and below, which is composed of the following components by weight: 64.50 parts of ethylene-butyl acrylate copolymer (EBA), 3.00 parts of low-density polyethylene (LDPE), 31.00 parts of conductive furnace black, 0.20 parts of antioxidant 1076 (octadecyl 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate), 0.20 parts of zinc stearate, 0.10 parts of dioctadecyl thiodipropionate, and 1.00 parts of di-tert-butyl dicumyl peroxide.

[0066] In this embodiment, commercially available antioxidant 1076 was used. Conductive carbon black was dried at 80°C for 6 hours. 31.00 parts of the dried conductive carbon black and 0.02 parts of antioxidant 1076 were added to toluene, and the mixture was ultrasonically sonicated at 400W for 5 minutes using an ultrasonic cell disruptor. The toluene was then removed at 90°C and the mixture was dried to obtain antioxidant pre-adsorbed carbon black.

[0067] EBA, LDPE, antioxidant pre-adsorbed carbon black, zinc stearate, dioctadecyl thiodipropionate and the remaining 0.18 parts of antioxidant 1076 were added to a torque rheometer, mixed at 165°C for 12 min, cooled and pelletized, and dried at 70°C for 6 h to obtain shielding material granules.

[0068] After preheating the shielding material granules at 60°C for 4 hours, they were mixed with 1.00 parts of di-tert-butyl peroxide diisopropylbenzene and allowed to stand at 55°C for 12 hours to allow the crosslinking agent to be fully absorbed, thus obtaining a cable shielding material for voltage levels of 500kV and below.

[0069] To verify the actual adsorption of antioxidant 1076 on the surface of conductive carbon black, the antioxidant pre-adsorbed carbon black obtained in this example was subjected to Soxhlet extraction with toluene to remove unadsorbed or weakly adsorbed free antioxidant 1076. The washed carbon black was then vacuum dried to constant weight at 80°C, and the temperature was increased from room temperature to 700°C at a rate of 10°C / min using a thermogravimetric analyzer (TGA) under a nitrogen atmosphere. Using untreated conductive carbon black as a blank sample, the actual adsorption amount of antioxidant 1076 on the surface of the conductive carbon black was calculated based on the weight loss difference of organic components within the range of 200-500°C. The test results show that the actual adsorption amount of antioxidant 1076 on the antioxidant pre-adsorbed carbon black in this example is 0.06% of the mass of the conductive carbon black, indicating that antioxidant 1076 can form a stable antioxidant pre-adsorbed layer on the carbon black surface.

[0070] Example 2

[0071] This embodiment 2 provides a cable shielding material for voltage levels of 500kV and below, which is basically the same as that in embodiment 1, except that the total amount of antioxidant 1076 is still 0.20 parts, of which the amount pre-adsorbed on the carbon black surface is 0.01 parts (accounting for 5% of the total amount), and the amount dispersed in the matrix resin is 0.19 parts (accounting for 95% of the total amount).

[0072] Example 3

[0073] This embodiment 3 provides a cable shielding material for voltage levels of 500kV and below, which is basically the same as that in embodiment 1, except that the total amount of antioxidant 1076 is still 0.20 parts, of which the amount pre-adsorbed on the carbon black surface is 0.04 parts (accounting for 20% of the total amount), and the amount dispersed in the matrix resin is 0.16 parts (accounting for 80% of the total amount).

[0074] Example 4

[0075] Example 4 provides a cable shielding material for voltage levels of 500kV and below, which is basically the same as Example 1, except that: a solvent-free hot premixing method is used, in which 31.00 parts of dried conductive carbon black and 0.02 parts of antioxidant 1076 are mixed at high speed at 95°C for 15 minutes to replace the solvent-assisted premixing step in Example 1; other components, dosages and preparation conditions are the same as in Example 1.

[0076] Comparative Example 1

[0077] Comparative Example 1 provides a shielding material that is basically the same as Example 1, except that: 0.20 parts of antioxidant 1076 are added together with the matrix resin and other additives (all located in the matrix resin phase) without pre-adsorption, that is, the amount of antioxidant pre-adsorbed on the carbon black surface is 0%, in order to verify the effect of canceling the pre-adsorption step on scorch performance, electrical conductivity and mechanical properties.

[0078] Comparative Example 2

[0079] Comparative Example 2 provides a shielding material that is basically the same as Example 1, except that: 0.20 parts of antioxidant 1076 are all pre-mixed with conductive carbon black (all located on the surface of carbon black), and no antioxidant is added to the matrix resin phase, that is, the pre-adsorption amount of antioxidant on the carbon black surface is 100%, in order to verify the effect of the lack of antioxidant protection in the matrix phase on thermo-oxidative stability when all antioxidants are pre-adsorbed on the carbon black surface.

[0080] Comparative Example 3

[0081] Comparative Example 3 provides a shielding material that is basically the same as that in Example 1, except that: 0.20 parts of antioxidant 1010 (pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate]) is used instead of antioxidant 1076. All antioxidants are added together with the matrix resin without pre-adsorption, in order to verify the effect of hindered phenolic antioxidants with different structures on the effect of the pre-adsorption strategy.

[0082] Comparative Example 4

[0083] Comparative Example 4 provides a shielding material that is basically the same as Example 1, except that: 0.20 parts of antioxidant 300 (4,4′-thiobis(6-tert-butyl-3-methylphenol)) are used to replace antioxidant 1076. All antioxidants are added together with the matrix resin without pre-adsorption, in order to verify the effect of hindered phenolic antioxidants with different structures on the pre-adsorption strategy.

[0084] Comparative Example 5

[0085] Comparative Example 5 provides a shielding material that is basically the same as Example 1, except that antioxidant 1076 is not added, but only zinc stearate and dioctadecyl thiodipropionate are added to verify the basic contribution of antioxidant to the overall performance of the shielding material.

[0086] To better understand the present invention, the following performance evaluation tests were performed on the embodiments and comparative examples.

[0087] Test 1

[0088] Test 1 is an electrical performance test. Referring to GB / T 3048.3-2007, the shielding materials obtained in each example and comparative example were hot-pressed and cross-linked for 15 min at 180℃ and 15 MPa to prepare test pieces with a thickness of 1 mm. After conditioning the test pieces at 23±2℃ for 24 h, the volume resistivity was measured using the four-electrode method. After thermal aging, the volume resistivity was measured again under the same conditions, and the resistivity change rate was calculated as (volume resistivity after aging - volume resistivity before aging) / volume resistivity before aging × 100%.

[0089] Test 2

[0090] Test 2 of this section tests processing performance and scorch performance. Referring to GB / T 16584-1996, the scorch time ts2 was determined at 140℃ using a rotorless vulcanizer (MDR), where ts2 is the time corresponding to a torque increase of 2 dN·m from its lowest value. According to GB / T 3682.1-2018, the melt mass flow rate was determined at 190℃ and under a 2.16 kg load using a melt flow rate meter.

[0091] Test 3

[0092] Test 3 is a mechanical property test. The tensile strength and elongation at break of the cross-linked specimens were determined using a universal testing machine in accordance with GB / T 1040.2.

[0093] Test 4

[0094] Test 4 is a thermal aging performance test. Referring to GB / T 2951.12-2008, the cross-linked test specimens were aged in an air oven at 135±2℃ for 168 hours; after removal and placement at 23±2℃ for at least 16 hours, the tensile strength was determined according to the method in Test 3. The tensile strength retention rate after thermal aging was calculated as tensile strength after aging / tensile strength before aging × 100%.

[0095] The test results for tests 1-4 above are shown in Table 1:

[0096] Table 1 Performance test results of each embodiment and comparative example

[0097]

[0098] As shown in Table 1, under the same total amount of antioxidant 1076, Example 1 achieved a volume resistivity of 105 Ω·cm, a 39% decrease compared to Comparative Example 1's 172 Ω·cm; the scorch time increased from 10.2 min to 16.5 min, a 62% improvement; the elongation at break increased from 162% to 218%, a 35% improvement; and the heat aging retention rate increased from 78% to 91%, a 13 percentage point improvement. The simultaneous improvement in all four indicators, rather than sacrificing one aspect for another, demonstrates the overall optimization effect of the pre-adsorption strategy.

[0099] In Comparative Example 2, all antioxidants were pre-adsorbed onto the carbon black surface. Although the scorch time was extended to 18.4 min, the volume resistivity increased to 138 Ω·cm, the elongation at break decreased to 198%, and the thermal aging retention rate decreased to 82%, all of which were inferior to those in Example 1. This indicates that the complete pre-adsorption of antioxidants onto the carbon black surface leads to a lack of antioxidant protection in the matrix phase, resulting in a significant decrease in the thermal and oxygen stability of the matrix, and the effect is not simply a matter of increasing performance.

[0100] The pre-adsorption ratio of Example 2 was 5%, and the pre-adsorption ratio of Example 3 was 20%. The overall performance of both was better than that of Comparative Example 1 (0% pre-adsorption) and Comparative Example 2 (100% pre-adsorption). This verifies that there is an optimal window for the pre-adsorption ratio. Too little pre-adsorption results in insufficient interface protection, while too much pre-adsorption leads to decreased matrix stability. The optimal value is between 5% and 20%, with 10% to 20% being the best.

[0101] Comparative Example 3, using AO-1010 as a substitute, saw its volume resistivity increase to 210 Ω·cm and its scorch time shorten to 9.5 min; Comparative Example 4, using AO-300 as a substitute, saw its volume resistivity increase to 185 Ω·cm and its scorch time shorten to 11.0 min, with all performance characteristics significantly inferior to Example 1. This indicates that the pre-adsorption strategy has a structure-specific effect, and not all hindered phenolic antioxidants can achieve the same results. AO-1076 type hindered phenols possess both hindered phenolic aromatic rings and octadecyl groups, and their unique advantage lies in the synergistic effect of π-π adsorption drive and improved compatibility. Although AO-1010 has multiple hindered phenolic groups, it lacks long-chain alkyl groups, resulting in insufficient compatibility with the matrix resin and an inability to effectively occupy high-energy sites on the carbon black surface; although AO-300 has a hindered phenolic structure, its sulfur bridge connection alters the electronic properties of the aromatic ring, leading to a decrease in π-π adsorption capacity.

[0102] Example 4 uses a solvent-free hot premixing method to prepare antioxidant pre-adsorbed carbon black. Its volume resistivity, scorch time, mechanical properties and thermal aging properties are similar to those of Example 1, indicating that when the pre-addition ratio of antioxidant 1076 and subsequent mixing conditions are kept unchanged, both solvent-assisted premixing and solvent-free hot premixing can form effective antioxidant pre-adsorbed carbon black.

[0103] Based on the above test results, this invention achieves a reduction in volume resistivity, an extension of scorch time, an improvement in mechanical properties, and improved thermal aging stability without increasing the total amount of antioxidant or introducing additional dispersing agents, by distributing antioxidant 1076 in a two-phase manner, with 5%-20% of its total amount used for premixing with conductive carbon black before being added to the matrix resin, and the remainder dispersed in the matrix resin phase during subsequent melt mixing. Comparative examples show that the overall performance is inferior to the 5%-20% two-phase distribution scheme when the pre-adsorption ratio is 0% or 100%. The performance significantly decreases when AO-1010 or AO-300, which lacks an octadecyl chain, is used as substitutes, and the performance is worst when no main antioxidant is added.

[0104] Various embodiments of the present invention may exist in the form of a range; it should be understood that the description in the form of a range is merely for convenience and brevity and should not be construed as a hard limitation on the scope of the invention; therefore, it should be considered that the range description has specifically disclosed all possible subranges and single numerical values ​​within that range. For example, it should be considered that the range description from 1 to 6 has specifically disclosed subranges such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., and single numbers within the range, such as 1, 2, 3, 4, 5, and 6, regardless of the range. Furthermore, whenever a numerical range is referred to herein, it means including any referenced number (fraction or integer) within the range referred to.

[0105] The above description is merely a specific embodiment of the present invention. Equivalent substitutions or modifications made by those skilled in the art without departing from the principles of the present invention should all fall within the protection scope of the present invention.

Claims

1. A cable shielding material for voltage levels of 500kV and below, characterized in that, The shielding material, by weight, is prepared from raw materials comprising the following components: The composition includes 58-76 parts of matrix resin, 24-38 parts of conductive carbon black, 0.12-0.30 parts of octadecyl 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, 0.05-1.0 parts of lubricant, 0.10-0.35 parts of antioxidant, and 0.5-2.0 parts of peroxide crosslinking agent. Of the total amount of octadecyl 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, 5%-20% is pre-adsorbed onto the surface of the conductive carbon black, and the remainder is dispersed in the matrix resin phase.

2. The shielding material according to claim 1, characterized in that, The matrix resin includes one or more of the following: ethylene-butyl acrylate copolymer, ethylene-vinyl acetate copolymer, ethylene-methacrylate copolymer, low-density polyethylene, and linear low-density polyethylene.

3. The shielding material according to claim 1, characterized in that, The conductive carbon black includes one or more of acetylene black, conductive furnace black, and Ketjen black. The specific surface area of ​​the conductive carbon black is 50-160 m² / g, the DBP oil absorption value is 100-380 mL / 100g, and the ash content is <0.5%.

4. The shielding material according to claim 1, characterized in that, The lubricant includes one or more of zinc stearate, calcium stearate, polyethylene wax, oxidized polyethylene wax, ethylene bis-stearamide, and organosilicon lubricants.

5. The shielding material according to claim 1, characterized in that, The antioxidant co-oxidant includes one or more of the following: dioctadecyl thiodipropionate, dilauryl thiodipropionate, and phosphite antioxidants.

6. The shielding material according to claim 1, characterized in that, The peroxide crosslinking agent includes one or more of dicumyl peroxide, bis-tert-butylperoxyisopropylbenzene, and 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane.

7. A method for preparing a cable shielding material of voltage level 500kV and below according to any one of claims 1-6, characterized in that, Includes the following steps: The conductive carbon black is dried to remove water. The dried conductive carbon black is then pre-mixed with 5%-20% of the total amount of octadecyl 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate to pre-adsorb the ester onto the surface of the conductive carbon black, thus obtaining antioxidant pre-adsorbed carbon black. The antioxidant pre-adsorbed carbon black, matrix resin, lubricant, antioxidant agent and the remaining octadecyl 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate were melt-blended and pelletized to obtain the compound. After preheating the compound, a peroxide crosslinking agent is added for liquid-phase impregnation and adsorption to obtain the cable shielding material for voltage levels of 500kV and below.

8. The method according to claim 7, characterized in that, The premixing temperature is 65-120℃, and the time is 5-30 minutes; The melting and mixing temperature is 120-180℃, and the time is 5-20 minutes; The preheating temperature is 50-75℃, and the time is 2-8 hours; The liquid phase impregnation adsorption temperature is 45-70℃, and the time is 6-16h.

9. The method according to claim 7, characterized in that, The premixing includes one of solvent-free hot premixing, solvent-assisted premixing, or melt spray premixing.

10. The application of any 500kV and below voltage level cable shielding material according to any one of claims 1-6 in the conductor shielding layer, insulation shielding layer or peelable semiconductive shielding layer of cross-linked polyethylene insulated cable of 110kV and above.